Attachment style dimensions are associated with neural activation during projection of mental states - Lai, Carlo; Ciacchella, Chiara; Altavilla, Daniela; Veneziani, Giorgio; Aceto, Paola; Cecchini, Marco; Luciani, Massimiliano (Frontiers in Human Neuroscience, 2022)
The aim of the present study was to investigate the association between attachment dimensions and neural correlates in response to the Rorschach inkblots. Twenty-seven healthy volunteers were recruited for the electroencephalographic registration during a visual presentation of the Rorschach inkblots and polygonal shapes. The Attachment Style Questionnaire (ASQ) was administered to participants. Correlations between the ASQ scores and standardized low-resolution brain electromagnetic tomography (sLORETA) intensities were performed. The Rorschach inkblots elicited several projective responses greater than the polygonal shapes (distortions, human and total movements, and embellishments). Only during the Rorschach inkblots presentation, discomfort with closeness and relationships as secondary subscales were negatively correlated with the activation of right hippocampus, parahippocampus, amygdala, and insula; need for approval subscale was negatively correlated with the activation of orbital and prefrontal cortex and left hippocampus. Moreover, the correlations between attachment dimensions and neural activation during the Rorschach inkblots were significantly higher compared to the same correlations in response to polygonal shapes. These findings suggest that attachment style can modulate brain activation during the projective activity of the Rorschach inkblots.